Regeneração in vitro de Parapiptadenia rigida (Bentham) Brenan - Nascimento, Paula Kielse Vargas do (2008)
The Parapiptadenia rigida (Bentham) Brenan is a native forest specie that can be used in the restoration of gallery forests and degraded areas. This work has the objective to develop the regeneration in vitro of P. rigida using explants of aseptic seedlings. In experiment 1, seeds of P. rigida were disinfected in 0.0, 2.5 and 5.0% of sodium hypochlorite during 5, 10, 15 and 30 minutes. A design completely randomized was used with 12 treatments and four repetitions by treatment, each repetitions had five seeds. It was evaluated the percentage of seeds sprouted at 10, 20 and 30 days, and the percentage of seeds aseptic in 30 days. In experiment 2, shoots of cotyledonal nodal segment and nodal segment were induced using 0.0, 0.25, 0.50 and 1.0 mg.L-1 of BAP or KIN. The design was completely randomized and 16 treatments were used, each treatment was constituted by five repetitions with six bottles each. The percentage of explants with shoots, the size of shoots, the number of leaves per shoots, the morphologic appearance of shoots, the percentage of callus on the base of explants and the size of callus were availed at 60 days. In experiment 3, named by rooting of explants, two tests were performed. Test 1 used cotyledonal nodal segment and nodal segments, both from shoots induction phase, and test 2 used shoots from cotyledonal nodal segment. At experiment 3, it was used IBA with concentration of 0, 0.25, 1.0 and 1.75 mg.L-1 and a design completely randomized, with 8 treatments. Test 1 was constituted by four repetitions with three bottles per repetition and test 2 was constituted by four treatments, each treatments constituted by four repetitions with five bottles per repetition. The percentage of rooting, the number of roots per explants, the length of the longest root, the percentage of explants with callus on the base and the average size of callus were availed at 60 days. In experiment 4, the plants were transferred to the substrate composed by Plantmax® and vermiculite, and the percentage of survival was availed at 60 days. The analysis of variance, the Tukey test and the regression analyzes were applied on data obtained from all experiments. In experiment 1, the highest percentages of germinations (76%) were found in the treatment with water and Tween 20 during 20 minutes. The second higher was the treatment with 2.5% of sodium hypochlorite during 30 minutes (70%). The highest percentage of disinfected seeds (81%) occurred in treatment with 2.5% of sodium hypochlorite during 30 minutes. In experiment 2, the dose of 0.50 mg.L-1 formed the largest size sprouts (0.50 cm) and the biggest number of leaves for sprout (3.60 leaves), independent of kind of phytoregulators. Experiment 3 presented the biggest number of roots was observed in segments cotyledonal nodal cotyledonary inoculated in medium containing 1.0 mg.L-1 of IBA (2.35 roots). In experiment 4, the highest percentage of survival was in plants derived from cotyledonal nodal segment in medium of rooting containing 1.0 mg.L-1 AIB. The segment cotyledonal nodal is better kind of explant for regeneration in vitro of the P. rigida than nodal segment.